Revestimento a base de compósito epóxi-bentonita/ZnO utilizando fiação por sopro em solução modificada - Veras, Tiago Neves (2015)
Brazil already produces more than 2 million barrels-per-day and this has a production forecast to increase in the coming years, when platforms had been operating at full potential. Increase in exploration directly affects the constituent alloy carbon steel to transport oil through the pipeline, increasing the oxidation caused mainly by sulfur elements and holders of hydrogen, whose main compound is H2S. Therefore, it is essential investments in the discovery of new methods to improve the protection and useful life of these materials. Given these problems, this work had been conducted to develop three different composites for adsorption of H2S composed by epoxy resin, bentonite particles, ZnO and ZnO supported on bentonite, as potential adsorbent materials, obtained by synthesis using the Pechini modified method. A study was conducted to investigate the behavior of the resin, using DSC with isotherms at 35, 50, 75 and 125C° and a dynamic rheometer for setting the temperature and time of heating for the application and reception of the particles using the Solution Blow Spinning technique. The bentonite was tested in different solvents with dispersant to form a suspension with the best stability. The concentration of 10% m/v in water was selected and the suspensions with Bentonite, ZnO and Bentonite/ZnO were prepared. The best coatings obtained were formed after heating the resin under 50°C with times of 16.3 and 33.3 minutes. The materials were analyzed with XRD, IR, UV-VIS and XRF. The suspensions were evaluated by a study of viscosity using a dispersant, with the good result only for the bentonite suspension. The composites were analyzed by SEM, XRD, optical microscopy and energy dispersive (EDS) to verify the presence of inorganic elements on the coating, allowing the process of adsorption.